Analysis of the Content of Da'wah Messages in the Film Teach Me Islam by Haris Suhud and Yunita R. Seragi - Tawvicky Hidayat; Hanisa, Hanisa (al-Afkar, Journal For Islamic Studies, 2025)
Islam is a religion of da'wah where Islam invites or calls us to goodness. Da'wah at this time is not enough if only through the pulpit to the pulpit because at this time very few teenagers listen to da'wah especially with the concept of majlis ta'lim or so on. So it is very effective if da'wah is delivered from several media, namely through music, newspapers, and others are da'wah through films. Just like the movie Teach Me Islam. The focus of research in this thesis is what are the messages of da'wah, money can be taken lessons in the film teach me Islam with the aim of knowing what are the messages of da'wah that can be learned in the film. In understanding the messages of da'wah in it, researchers use Roland Barthes' semiotic analysis where the analysis has two levels, namely denotation and connotation. The type of research used by researchers is qualitative descriptive research which has the meaning of qualitative research in the form of words, pictures, and not numbers. The result of this research is where the film Ajari Aku Islam shows that in it there is a message of da'wah in the categories of shari'ah, Akidah and Akhlak. The message of shari'ah da'wah is to attach importance to prayer, not to contact non-muhrim, to keep views. While the message of da'wah akidah is to learn Islam, love Allah SWT, and what is the message of moral da'wah is to have good manners, always dhikr to Allah SWT, and please help. The conclusion of this study is that the film Ajari Me Islam is a religious film that has an interesting story and has a lot of da'wah messages teaching us to always be friendly and humble to everyone and not look at differences between ethnicity, race and religion because humans are social creatures who cannot live without the help of others.